Radium-223 as an Additional Therapeutic Strategy in Highly Selected Patients With Metastatic Breast Cancer: A Case Report - Houssiau, Hélène; Duhoux, Francois P.; François, Didier; Seront, Emmanuel (Frontiers in Oncology, 2022)
Radium-223 is commonly used in metastatic prostate cancer, targeting specifically bone metastases. The use of radium-223 remains, however, poorly evaluated in metastatic breast cancer. We report a case of radium-223 treatment in a 59-year old patient with bone-only metastatic disease that progressed on multiple lines of systemic treatments. Radium-223 was very well tolerated and resulted in a regression of activity of bone metastases and in a 6-month progression free survival. However, progression occurred in liver, reflecting the fact that radium-223 should be combined to other systemic agents. This suggests that this therapeutic option is feasible and could be proposed in highly selected patients with bone metastatic disease outside of the prostate cancer field. Positron Emission Tomography appears also as a valuable tool for evaluation of radium-223 efficacy.